Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.3 Exercises - Page 126: 79


$f’(x) = \frac{6}{(x+2)^{2}}$ $g’(x) = \frac{6}{(x+2)^{2}}$ The slope of f(x) is equal to the slope of g(x). They are parallel fucntions.

Work Step by Step

Quotient rule: $\frac{d}{dx}$$\frac{f(x)}{g(x)}$ = $\frac{g(x)f’(x)-f(x)g’(x)}{g(x)g(x)}$ $f(x) = \frac{3x}{x+2}$ $f’(x) = \frac{(x+2)(3)-(3x)(1)}{(x+2)^{2}}$ = $\frac{3x+6-3x}{(x+2)^{2}}$ = $\frac{6}{(x+2)^{2}}$ $g(x) = \frac{5x+4}{x+2}$ $g’(x) = \frac{(x+2)(5)-(5x+4)(1)}{(x+2)^{2}}$=$\frac{5x-10-5x-4}{(x+2)^{2}}$=$\frac{6}{(x+2)^{2}}$
Small 1514355253
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.